Living temporaneity in the student housing. A process and product challenge - Oscar Eugenio Bellini; Federica Donadoni (Agathón)
In University residences, the categories of stability and durability, which are usually attributed to architecture, do not necessarily have to be applied. The temporariness of these structures, which may seem a contradiction – if not an oxymoron – has become one of the design paradigms that define the essential element of this form of living. In student housing, the temporary character can take on a plurality of meanings: constructive, functional, of use, etc. The contribution illustrates how University residences have now freed themselves from a monotonous and standardized image and have reached interesting levels of quality, succeeding in giving credible answers on the technological and figurative level that could also be assumed in our country.